2013
DOI: 10.1016/j.scr.2013.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin extra domain A (EDA) sustains CD133+/CD44+ subpopulation of colorectal cancer cells

Abstract: Fibronectin is a major extracellular matrix glycoprotein with several alternatively spliced variants, including extra domain A (EDA), which was demonstrated to promote tumorigenesis via stimulating angiogenesis and lymphangiogenesis. Given that CD133+/CD44+ cancer cells are critical in tumorigenesis of colorectal cancer (CRC), we hypothesize that fibronectin EDA may promote tumorigenesis by sustaining the properties of CD133+/CD44+ colon cancer cells. We found that tumor tissue and serum EDA levels are substan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 60 publications
(79 reference statements)
1
38
0
Order By: Relevance
“…Fibronectin and Lgr5 mRNA expression were both down-regulated upon treatment with Sal in SW620 and HT29 cells. The importance of Fibronectin and its spliced variant extra domain A (EDA) has been characterized as essential for the phenotype and the tumorigenic properties of CD133 + /CD44 + CRC cells [40]. Furthermore, a correlation between Fibronectin EDA-level and stage of disease and chemoresistance of CRC patients was reported [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fibronectin and Lgr5 mRNA expression were both down-regulated upon treatment with Sal in SW620 and HT29 cells. The importance of Fibronectin and its spliced variant extra domain A (EDA) has been characterized as essential for the phenotype and the tumorigenic properties of CD133 + /CD44 + CRC cells [40]. Furthermore, a correlation between Fibronectin EDA-level and stage of disease and chemoresistance of CRC patients was reported [40].…”
Section: Discussionmentioning
confidence: 99%
“…The importance of Fibronectin and its spliced variant extra domain A (EDA) has been characterized as essential for the phenotype and the tumorigenic properties of CD133 + /CD44 + CRC cells [40]. Furthermore, a correlation between Fibronectin EDA-level and stage of disease and chemoresistance of CRC patients was reported [40]. Given that silencing of EDA resulted in downregulation of Wnt/β-catenin signaling and the inhibitory effects of Sal on Fibronectin expression in our study, Sal might be regarded as an inhibitor of the regulatory Fibronectin/Wnt/β-catenin signaling loop in human CRC cells [41].…”
Section: Discussionmentioning
confidence: 99%
“…Dose dependent reductions in VEGF-C were observed following cancer cell treatment with an inhibitor of PI3K 19. Aside from a role in angiogenesis, ED-A fibronectin was reported to be upregulated in patient colorectal tumors, especially those that were of advanced stage 20. Investigating CD133 + /CD44 + colorectal tumor cells, a subset of cells believed to be responsible for colon cancer initiation, the authors found that these cells expressed higher levels of the ED-A receptor α 9 β 1 and further demonstrated that ED-A interaction with α 9 β 1 was required for tumor cell proliferation 20.…”
Section: Tumor Progressionmentioning
confidence: 99%
“…On the other hand, the lack of FN in metastatic niche would lead to decreased metastases formation (Figure 2C). For example, a recent study demonstrated that silencing EDA-FN reduced metastasis of colon cancer cells 57 . In companion with EMT, mesenchymal-to-epithelial transition (MET) is also crucial for metastasis formation.…”
Section: Upregulated Fibronectin Is a Cancer Markermentioning
confidence: 99%